Terapia periodontal no quirúrgica (2012)
ABSTRACT: In the treatment of periodontal diseases, we can rely on nonsurgical periodontal therapy, which has been scientifically proven as its effectiveness has been recognized. The main objective of this article is to demonstrate the usefulness of nonsurgical periodontal therapy, as evidenced in several studies that serve as guidelines, as well as microbiological aspects, effects on tissues and the importance of maintenance therapy after treatment completion. Methods: a review was conducted in order to revise this topic considering key periodontal concepts as a guideline. Results: nonsurgical periodontal therapy (NSPT) is a procedure that cannot and should not be carried out in a few sessions; the time required for its completion is extended as necessary in order to achieve cleaning and adjustment of the roots as completely as possible. Conclusions: Several authors have reported that reduction of microbiota remains between 14 and 180 days after therapy. This explains the regular periodontal maintenance appointments. They also indicate that the critical aspect of this therapy is not the choice between a surgical or a nonsurgical procedure, but a detailed and thorough cleaning by the dental professional and the good level of oral hygiene achieved by the patient.